التعلم الجوال وصعوبات تطبيقه في العملية التعليمية من وجهة نظر أعضاء الهيئة التدريسية في كلية التربية بجامعة البعث - حسن، رنا; ديب، أوصاف علي (جامعة البعث, 2016)
The study aimed to know the reality of mobile learning in Baath University from the viewpoint of faculty members, so it has been preparing a questionnaire applied to a random sample which consist of (32) member. The study has revealed the following results: Sample The study found that mobile learning importance in providing immediate feedback and the elimination of free time and to facilitate the exchange of information with colleagues, and the achievement of the Internet and search for information easy connectivity process. The most important obstacles that faculty members felt they constitute an obstacle to the application of mobile learning effectively in the educational process has been the weakness of the Internet, the lack of adequate training on the preparation of mobile learning system software skills, and high material cost for portable devices.
هدفت الدراسة إلى تعرف آراء أعضاء الهيئة التدريسية في كلية التربية بجامعة البعث في واقع استخدام التعلم الجوال في العملية التعليمية وصعوبات تطبيقه، لذا تم إعداد استبانة طبقت على عينة عشوائية من أعضاء الهيئة التدريسية في كلية التربية بجامعة البعث والبالغ عددهم (32) عضوا. وتوصلت الدراسة إلى النتائج الآتية: أهمية التعلم الجوال في توفير فرص جديدة للبحث عن المعلومات وتبادل الخبرات بين المتعلمين، وتحقيق أهداف التعلم عن بعد وتنمية مهارات التعلم الذاتي. ووجدت عينة الدراسة أن للتعلم الجوال أهمية في تقديم التغذية الراجعة الفورية وتسهيل عملية تبادل المعلومات مع الزملاء، وتحقيق اتصال سهل بالإنترنت والبحث عن المعلومات. أما أهم الصعوبات التي رأى أعضاء الهيئة التدريسية أنها تشكل عائقا أمام تطبيق التعلم الجوال بفاعلية في العملية التعليمية فقد كانت ضعف شبكة الأنترنت، عدم توفر تدريب كاف على مهارات إعداد برامج نظام التعلم الجوال، ارتفاع التكلفة المادية للأجهزة الحديثة المحمولة.
Keywords: التعلم الجوال -- أعضاء الهيئة التدريسية -- جامعة البعث